2007
DOI: 10.1007/s10571-007-9167-8
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Changes of p27kip1 and Skp2 Expression in Injured Rat Sciatic Nerve

Abstract: S phase kinase-associated protein 2 (Skp2), an F-box protein, is required for the ubiquitination and consequent degradation of p27(kip1). Previous reports have showed that p27(kip1 )played important roles in cell cycle regulation and neurogenesis in the developing central nervous system. But the distribution and function of p27(kip1 )and Skp2 in nervous system lesion and regeneration remains unclear. In this study, we observed that they were expressed mainly in both Schwann cells and axons in adult rat sciatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 26 publications
(26 reference statements)
2
6
0
Order By: Relevance
“…However, we found that suppression of p57kip2 leads to cell cycle exit. This can be explained by the observed induction of the related CKIs p27kip1 and p21cip1 and is in accordance with previously published results (25,26). Currently we have no evidence that the members of the INK4 family, namely p15, p16, p18, and p19, are involved in regulating Schwann cell cycle exit in response to p57kip2 suppression.…”
Section: Discussionsupporting
confidence: 92%
“…However, we found that suppression of p57kip2 leads to cell cycle exit. This can be explained by the observed induction of the related CKIs p27kip1 and p21cip1 and is in accordance with previously published results (25,26). Currently we have no evidence that the members of the INK4 family, namely p15, p16, p18, and p19, are involved in regulating Schwann cell cycle exit in response to p57kip2 suppression.…”
Section: Discussionsupporting
confidence: 92%
“…p27 kip1 has been implicated in promoting cell cycle arrest of neural progenitors during embryogenesis [6,7], in regulating the division of transit amplifying progenitors in the adult subventricular zone [8]. These data confirmed the effect of p27 kip1 on central nervous system (CNS) development, and we recently reported its expression in injured sciatic nerve [9] and injured spinal cord [10]. FKHRL1 (FOXO3a), which is a forkhead transcription factor of the forkhead box, class O (FOXO) subfamily, is a target of phosphatidylinositol 3-kinase (PI3-K) signaling, which regulates their activity via phosphorylation mediated by protein kinase B/Akt and serum and glucocorticoidinduced kinase (SGK) [11].…”
Section: Introductionsupporting
confidence: 64%
“…p27 kip1 , as a member of Cip/Kip family of cyclindependent kinase inhibitors, plays an important role in cell cycle regulation and neurogenesis in the developing CNS. We recently reported p27 kip1 was down-regulated in the injured sciatic nerve [9] and the lumbar spinal cord after sciatic nerve injury [28], and the down-regulation of p27 kip1 was very likely to be involved in the regeneration process after peripheral nerve injury. Previous studies showed down-regulated p27 kip1 through FOXO transcriptional inhibition was associated with multitude cell types proliferation, including hematopoietic cells [13], tumour cell strains [14], T cells [15] and endothelial cells [29,30].…”
Section: Discussionmentioning
confidence: 98%
“…Pirh2 Expression is Up-regulated after Brain Injury and Inversely Correlated with p27 kip1 Expression Previous study conducted by our group has shown that p27 kip1 expression was reduced during the repair process after injury in nerve system (Liu et al 2010;Shen et al 2008). Western blot and immunohistochemistry were performed to investigate the changes of Pirh2 and p27 kip1 after brain injury.…”
Section: Resultsmentioning
confidence: 99%
“…In the central nervous system (CNS), p27 kip1 plays important roles in promoting cell cycle arrest of neural progenitors during embryogenesis (Carruthers et al 2003;Miyazawa et al 2000), regulating the division of transit amplifying progenitors in the adult subventricular zone (Doetsch et al 2002) and influencing neuronal differentiation and neuronal migration in the cerebral cortex (Nguyen et al 2006). Moreover, previous study showed that p27 kip1 expression was reduced during the repair process after injury in adult brain, spinal cord and dorsal root ganglia (Liu et al 2010;Shen et al 2008).…”
Section: Introductionmentioning
confidence: 95%